Efektivitas Layanan Bimbingan Kelompok Menggunakan Mind Mapping Pada Career planning Anak Asuh - Romadhon, Hilman; Eni Nur’aeni; Yogi Damai Syaputra (Institut Agama Islam Negeri Curup, 2024)
This study aims to improve career planning through group guidance using the mind mapping technique. The research employs a quantitative method with a pre-experimental one-group pretest-posttest design. The study was conducted at Panti Daarul Hasanah Karawang with a sample size of 10 people. The research instrument was a career planning questionnaire using a Likert scale. The intervention was given in 4 sessions. Data were analyzed using the Wilcoxon test and n-gain test to assess effectiveness. Data analysis was performed using the Wilcoxon test and n-gain through SPSS version 25. The results showed that the career planning of the foster children before the intervention was in the very low and low categories. After the intervention, their career planning increased to the medium, high, and very high categories. The Wilcoxon test analysis showed a significance value of 0.005 < 0.05, indicating that the group guidance intervention using mind mapping was effective in improving the career planning of foster children. Furthermore, the n-gain test used to measure the effectiveness of the treatment showed an n-gain value of 98.5%, meaning that this group guidance was highly effective in enhancing the foster children's career planning